Massive hydration-driven swelling of layered perovskite niobate crystals in aqueous solutions of organo-ammonium bases. Issue 9 (8th November 2017) - Song, Yeji; Iyi, Nobuo; Hoshide, Tatsumasa; Ozawa, Tadashi C.; Ebina, Yasuo; Ma, Renzhi; Yamamoto, Shinya; Miyamoto, Nobuyoshi; Sasaki, Takayoshi
Abstract : A systematic understanding on the osmotic swelling of layered niobate crystals using various amines is reported. Abstract : Osmotic swelling behaviors in layered perovskite niobate were examined in aqueous solutions containing three types of amine-related agents including quaternary ammonium hydroxides and tertiary aminoethanol. Platelet microcrystals of a protonated layered perovskite niobate, HCa2 Nb3 O10 ·1.5H2 O, were found to show enormous swelling in the aqueous solutions, which was clearly recognized by the noticeable expansion of the sample volume over 100-fold. Optical microscopy observations revealed that the crystals underwent accordion-like elongation in the layer-stacking direction up to several ten-fold the initial thickness. Small-angle X-ray scattering measurements of swollen samples indicate the expansion of interlayer separation ranging from ∼20 nm to over 100 nm, which is primarily governed by the concentrations of the amine-related agents. The magnitudes of the interlayer separation were comparable to those of the macroscopic swelling. The degree of swelling was progressively suppressed with further increasing concentration, and this suppression trend was related to the amines.